1998
DOI: 10.1093/intimm/10.12.1923
|View full text |Cite
|
Sign up to set email alerts
|

A further link between innate and adaptive immunity: C3 deposition on antigen-presenting cells enhances the proliferation of antigen-specific T cells.

Abstract: Murine cells of the B lymphoblastoid line A20 and concanavalin A-elicited peritoneal macrophages are shown to activate and fix C3 fragments covalently when incubated in fresh, autologous serum under conditions allowing the initiation of the alternative complement pathway. For the detection of cell-bound C3, cytofluorimetry was performed using FITC-labeled F(ab')2 fragments of anti-mouse C3. Cell-bound C3 fragments are not internalized or shed by the cells under culture conditions for at least two hours. When t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
47
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 29 publications
2
47
0
Order By: Relevance
“…Although the underlying mechanisms are still unclear, it has been reported that C3 deposition on APCs augments T cell proliferation (40,45). Taken together, these reports suggest that lack of C3 activity can also affect the efficiency of Ag presentation, thereby limiting the expansion of LCMV-specific CD8 T cells in vivo.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the underlying mechanisms are still unclear, it has been reported that C3 deposition on APCs augments T cell proliferation (40,45). Taken together, these reports suggest that lack of C3 activity can also affect the efficiency of Ag presentation, thereby limiting the expansion of LCMV-specific CD8 T cells in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…CR1/CR2 signaling in B cells regulates activation threshold, Ag uptake, processing and presentation, isotype switching, and generation of memory B cells (9). Moreover, expression of CR1/CR2 on T cells has been reported, and may promote binding between the APC and T cells via C3 (16,40,45). Therefore, C3 can regulate T cell responses by interacting directly with T cells or indirectly via APCs.…”
Section: Discussionmentioning
confidence: 99%
“…It has become apparent that the stimulation and activation of T cells depend not only on the presentation of the peptide-MHC complex by APCs in lymph nodes or secondary lymphoid organs but also include various other factors (46). Studies in the literature suggest that the complement plays an important role in antigen presentation by APCs as well as antigen-specific T cell responses (20,21,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing candidate gene for Ciaa3 is the complement 3 gene (C3) which maps at the extreme centromeric end of chromosome 9 (62). Activation products of C3 enhance both antigen-specific T cell activation (63) and subsequent autoantibody formation (64). C3b-antigen complexes promote macrophage processing of antigen and presentation of antigenic peptides to T cells (65).…”
Section: Discussionmentioning
confidence: 99%